Faktor-faktor yang Mempengaruhi Minat UMKM untuk Menggunakan Aplikasi SIAPIK di Kota Balikpapan - Febby Fitria; Rihfenti Ernayani; Ika Makherta Sutadji (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to determine the interest of MSMEs in using the SIAPIK application in Balikpapan City. The data used are primary data collected online via Google Form and offline directly. The data analysis method uses the Partial Least Square-Structural Equation Model (PLS-SEM). The results of the analysis show that perceptions of usefulness, perceptions of ease of use, and security have a significant effect on the interest of MSMEs in using the SIAPIK application. While trust and risk perception do not have a significant effect on the interest of MSMEs in using the SIAPIK application.